Influences on uptake of a community occupational therapy intervention for people with dementia and their family carers. (January 2019) - Field, Becky; Coates, Elizabeth; Mountain, Gail
Introduction: Health policy promotes living well with dementia. Occupational therapists deliver interventions to support people with dementia and family carers to live well. This study aimed at identifying influences on uptake of a community occupational therapy intervention by people with dementia and carers, as little evidence about this topic exists. Method: Seventeen semi-structured, paired interviews with people with dementia and carers were conducted as part of the 'Valuing Active Life in Dementia' research programme. A secondary, qualitative analysis of these interviews explored influences on uptake of the intervention. Findings: Four main themes were identified: 'Grabbing at straws and keen to take part'; 'We're trying to put a routine in'; 'We didn't know what to expect', and 'Give it a go'. Factors identified as potentially influencing uptake included whether the intervention was perceived as potentially meeting needs for support and activity, and whether participants were struggling to adjust or cope. Conclusion: Despite limited expectations or apprehension, uptake of this intervention was demonstrated. Understanding why people with dementia and carers accept intervention offers can inform what occupational therapists provide and how it is offered. Further research is required to determine the occupational therapy interventions people with dementia and carers might find supportive at different stages of the disease trajectory.